Optimizing Students’ Learning Achievement in Physical Education, Sports, and Health Subjects Through Pencak Silat Learning at Kyai Zakariya's Outstanding Elementary School - Oktavian, Muhamad Fikri Donny; Kusmawati, Wiwik; Pradipta, Anangga Widya; Artanty, Ary (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to improve students' learning achievement in Physical Education, Sports, and Health (PJOK) subjects through the implementation of pencak silat learning. The subjects of this study were 20 students of class V SDI Unggulan Kyai Zakariya. The research method used was Classroom Action Research (CAR) with two cycles. Data collection techniques used observation, achievement tests, and documentation. The results of the study showed that the implementation of pencak silat learning can improve students' learning achievement, marked by an increase in the average value from 65.5 in cycle I to 80.5 in cycle II. Thus, pencak silat-based learning is effective in improving motivation and learning outcomes of PJOK.